2014
DOI: 10.1038/cdd.2014.158
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection requires the functions of the RNA-binding protein HuR

Abstract: Alterations in the functions of neuronal RNA-binding proteins (RBPs) can contribute to neurodegenerative diseases. However, neurons also express a set of widely distributed RBPs that may have developed specialized functions. Here, we show that the ubiquitous member of the otherwise neuronal Elavl/Hu family of RNA-binding proteins, Elavl1/HuR, has a neuroprotective role. Mice engineered to lack exclusively HuR in the hippocampal neurons of the central nervous system (CNS), maintain physiologic levels of neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 78 publications
1
47
0
Order By: Relevance
“…On the other hand, we found that HuR-expressing cells are more efficient energy producers than corresponding control cells. Recent studies with mouse models have begun to link HuR to mitochondrion-regulated processes (59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found that HuR-expressing cells are more efficient energy producers than corresponding control cells. Recent studies with mouse models have begun to link HuR to mitochondrion-regulated processes (59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…The neurodegeneration observed in mice lacking HuR in hippocampal neurons was also attributed to mitochondrial dysfunction due to an inability of the neurons to defend against oxidative damage or maintain energy homeostasis (Skliris et al 2015). Similarly, in a mouse model of amyotrophic lateral sclerosis (ALS), mutant SOD sequestered HuR, thereby preventing its interaction with cellular mRNAs and triggering mitochondrial dysfunction, oxidative stress, and cell death (Lu et al 2009).…”
Section: Consequences Of Rmrp Mislocalizationmentioning
confidence: 99%
“…On the other hand, HuR has been linked extensively to the maintenance of organ homeostasis, for example, by modulating gastrointestinal function, cell senescence, cell proliferation, myogenesis, and the stress and immune responses . HuR has also been implicated in numerous disease processes, including the prevention of neurodegenerative disease (Skliris et al 2015) and the exacerbation of cancer, cardiovascular pathologies, and aberrant immune responses Suresh Babu et al 2015).…”
Section: Consequences Of Rmrp Mislocalizationmentioning
confidence: 99%
“…Like the circadian clock mechanism, evidence indicates ELAVL1 is regulated by pyruvate kinase in glioblastoma cells (Mukherjee et al, 2016), suggesting another way that energy demands within the organism might also alter SCN cell networks. Alternatively, ELAVL1 may serve in a non‐clock function in the SCN by preventing excitotoxic damage though intracellular Ca 2+ (Skliris et al, 2015); the SCN is unique among hypothalamic nuclei in receiving substantial glutamatergic retinal afferents, and protection from excessive sensory stimuli would be expected.…”
Section: Discussionmentioning
confidence: 99%